Different This Time? The Prospects of CCS in the Netherlands in the 2020s - Akerboom, Sanne; Waldmann, Svenja; Mukherjee, Agneev; Agaton, Casper; Sanders, Mark; Kramer, Gert Jan (Frontiers in Energy Research, 2021)
Carbon Capture and Sequestration (CCS) has been recognized as an important means of mitigating global climate change, but apart from several pilots, it has not yet been successfully implemented on the large scale needed to live up to the expectations as a mitigation method. In Netherlands, the option of CCS has been the subject of debate for a long time, as three unsuccessful projects – two onshore in Barendrecht and the Northern regions, and one offshore near the Port of Rotterdam – demonstrate. Nevertheless, CCS has been accorded an important place in the current Dutch climate policies, being expected to contribute up to 7 Megaton of CO2 reduction. This is reflected in a fresh crop of CCS project plans. For the most, these plans have a long way to go from the drawing board to actual operations due to the technical, economic, legal and societal challenges ahead. In this article we review the status and possibilities of CCS in Netherlands based on an analysis of existing literature in the relevant disciplines. First, a brief overview of the technology options for carbon capture and storage or utilization is given. This is followed by a detailed analysis of the governmental support for CCS, given the vital role that fit-for-purpose legal frameworks and policy instruments will play in CCS deployment. Technical, legal and policy uncertainties translates into factors inhibiting CCS investment and so the paper then presents a CCS investment project to illustrate how such risks affect the business case for CCS. Finally, bearing in mind that societal acceptance has proved to be a major barrier for CCS, both in Netherlands and elsewhere, the conditions that enhance public acceptance of CCS are examined. Our work shows that while CCS is technically a straightforward proposition, its deployment has historically been hindered by the lack of a sound business case and a compelling and stable socio-technical narrative. The main argument in favor of CCS today is that it offers a transition pathway for rapidly and massively reducing CO2 emissions beyond what could be accomplished by alternative methods like electrification and renewable fuels in near future. The introduction of new financial instruments, increased government support and an improvement in social engagement appear to have enhanced the prospects of CCS in Netherlands, but we feel it is premature to assume that this time everything is different.